An Arbitrary Lagrangian-Eulerian, coupled neutronics-shock physics model for the analysis of shockwave implosion of solid fissile materials. (15th June 2020) - Cervi, E.; Cammi, A.
Highlights: A coupled neutronics-shock physics solver for imploding fissile solids is presented. A hydrodynamic model is developed to simulate shock propagation in solids. Different neutron transport models are developed to evaluate the neutron flux. An ALE moving mesh is implemented to describe shock-induced deformations. All the developed models are verified/validated with many test cases. Abstract: The aim of this work is to present a coupled neutronics-shock physics model for the study of shockwave compression of solid fissile materials. The shock-physics solver implements multi-material continuum mechanics balance equations, a hydrodynamic material response model and a dynamic mesh to describe shock-induced deformations in solid bodies. In addition, an Arbitrary Lagrangian-Eulerian (ALE) formulation of the governing equations is adopted, in order to avoid mesh distortion and tangling problems in case of large deformations. As for neutronics, a multigroup SP3 neutron transport model is selected for the estimation of the neutron flux. Several case studies are presented to validate the developed models, demonstrate the coupling between the two physics and highlight the advantages of the ALE approach. The proposed model can be a useful tool for the simulation of shock implosion of fissile materials, such as in subcritical plutonium experiments or in reactivity accidents initiated by strong energetic events.